Delete the story and its implications between the traditional style and the aesthetics of the receipt - Muhamad , Amir (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The phenomenon of deletion of the news contributes directly to the creation of infinite signs swim in the consciousness of the PATH conforms to the creative space and the breadth of its horizons. The production of additional signs of problem on the recipient is by adding the receiver a new view of the article to the elements absent in the structure and the ambiguity based on multiple possibilities of meaning It fills the gaps that permeate the elements present in creativity. The Balagians count this art - I mean obliteration - as a setback, and an intentional goal. It is an aesthetic and pedagogical addition that the creator uses to convey his affective experience to the recipient and influence him, to cut off the sarcasm and boredom from what he reads. The purpose of deleting the news is related to the conditions of the soul distributed between the path and the receiver, and are related to the circumstances and circumstances that call for the deletion, which are many and varied.